National Geographic Kids almanac 2025. (National Geographic kids., 2024)
The most exciting edition yet of the world's best-selling almanac for kids! Including animals, space, inventions, history, and more, it's a one-stop shop for every curious kid! Kids who want to know everything about everything need the National Geographic Kids Almanac. This latest edition is packed with incredible photos, tons of fun facts, crafts, activities, and fascinating features about animals, science, nature, technology, conservation, and more. Practical reference material, including fast facts and maps of every country, has been fully updated. Homework help on key topics is sprinkled throughout the book. A must-have book for curious kids.